Improved upper limits on the stochastic gravitational-wave background from 2009-2010 LIGO and Virgo data - LIGO Scientific Collaboration (2014)
Paper producido por "The LIGO Scientific Collaboration and the Virgo Collaboration". (En el registro se mencionan solo algunos autores de las decenas de personas que participan).